Causes for exclusion of living kidney donors at the transplant service of a thirdlevel hospital in northwestern Mexico - K, Guzmán-Flores (2023)
Objective: To identify the causes for exclusion of living kidney donors at a third-level hospital in northwestern Mexico. Materials and methods: An observational, cross-sectional, descriptive and retrospective study, in which the medicalrecords of candidates for living kidney donation were evaluated from January 1, 2019 to December 31, 2021. Results: Out of the 30 selected records, only 6.6 % (2) were chosen as donors, i.e., the rejection rate of the potential candidates was 93.3 % (28). The average age was 40.7 years; when divided into age groups, it was observed that 7.44 % were ≤ 39 years, 5.31 % were ≥ 50 years and 4.25 % were in the 40–49 age range. The main pathologies that caused therejection of living donors were chronic diseases such as unknown renal disease, obesity, diabetes mellitus, systemic hypertension and heart diseases, which accounted for 60.7 %. The desire to donate was more frequent among blood relatives than non-blood relatives. In the case of blood relatives, i.e., siblings, parents, children, uncles, aunts, etc., 64.2 % were rejected, while 34.7 % of non-blood relatives, including spouses and friends, were rejected.Conclusions: Based on the body mass index (BMI), the results showed that overweight and obesity were the main causes of exclusion, a situation that is consistent with the Mexican epidemiological profile. The number of living donors at ourcenter has been reduced because most of the population is not healthy and has obesity, which affects the willingness to be a candidate for living kidney donation.